2014
DOI: 10.1016/j.ajpath.2014.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Cell-of-Origin for Fibroblasts Comprising the Fibrotic Reticulum in Idiopathic Pulmonary Fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is a progressive disease of the middle aged and elderly with a prevalence of one million persons worldwide. The fibrosis spreads from affected alveoli into contiguous alveoli, creating a reticular network that leads to death by asphyxiation. Lung fibroblasts from patients with IPF have phenotypic hallmarks, distinguishing them from their normal counterparts: pathologically activated Akt signaling axis, increased collagen and α-smooth muscle actin expression, distinct gene ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
121
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 75 publications
(137 citation statements)
references
References 65 publications
10
121
0
1
Order By: Relevance
“…Gene expression profiling of IPF MPCs distinguished them from MPCs isolated in a similar manner from the lungs of patient controls, with enrichment of genes associated with diseaserelevant ontologies (14). Specifically, we found that IPF MPCs express higher levels of S100A4 compared with control MPCs (14).…”
Section: Introductionmentioning
confidence: 70%
See 4 more Smart Citations
“…Gene expression profiling of IPF MPCs distinguished them from MPCs isolated in a similar manner from the lungs of patient controls, with enrichment of genes associated with diseaserelevant ontologies (14). Specifically, we found that IPF MPCs express higher levels of S100A4 compared with control MPCs (14).…”
Section: Introductionmentioning
confidence: 70%
“…Specifically, we found that IPF MPCs express higher levels of S100A4 compared with control MPCs (14). S100A4, a calcium binding protein, is upregulated in cancer stem cells, where it controls proliferation, differentiation, and metastasis (15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations